Upaya Pelaksanaan Pembangunan Kepariwisataan di Kabupaten Sampang : Studi: Implementasi Pasal 8 Ayat (1) Undang-Undang No. 10 Tahun 2009 tentang Kepariwisataan - Ikfina Himmati Faricha; Zilda Khilmatus Shokhikah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Sampang regency, located on Madura Island, is one of the districts that has abundant natural resources. There are various kinds of tourism potential in Sampang Regency. Tourism Management in Sampang Regency requires integrated and structured planning in order to improve the quality of existing tourism. One form of tourism planning in accordance with Article 8 paragraph (1) of Law No. 10 of 2009 on tourism, namely with the Master Plan of Tourism Development (RIPPARKAB), but until now the Sampang Regency government has not passed local regulations governing RIPPARKAB. The method used in this study is empirical juridical method, where this study was conducted by examining the actual circumstances or real circumstances that occur in society with the aim of knowing and finding the facts and data needed. The results showed that, Sampang Regency government efforts in the process of Tourism Development is to establish a decree of the Regent who set an area into a tourist spot. In addition, the Sampang Regency government has also drafted and will soon pass a regional regulation on RIPPARKAB as a guideline and implementation of Article 8 paragraph (1) of Law No. 10 of 2009 on tourism.